The Resource-Saving Technology of Aluminum Nitride Obtaining During Combustion of Aluminum Nanopowder in Air; MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Ilyin A. P. Aleksandr Petrovich (2016, 2016)
Title screen